Functionalised Biferrocene Systems towards Molecular Electronics. Issue 2 (30th November 2016) - Wilson, Lucy E.; Hassenrück, Christopher; Winter, Rainer F.; White, Andrew J. P.; Albrecht, Tim; Long, Nicholas J.
Abstract : Biferrocene systems offer a motif that incorporates multiple redox‐active centres, enabling redox control, high levels of stability and near perfect conductance levels, and thus is an ideal participant within future molecular electronic systems. However, the incorporation of biferrocene can be restricted by current synthetic routes. Herein, we discuss a new method for the synthesis and incorporation of biferrocenyl motifs within extended conjugated systems. We have synthesised a family of compounds featuring biferrocenyl–ethynyl units with various pendant heteroaromatic linkages. The new compounds are probed with use of cyclic voltammetry, UV/Vis/near‐infrared (NIR) spectroelectrochemistry and X‐ray crystallography to gain further understanding of their structural and electronic properties. Abstract : A new method for the synthesis and incorporation of biferrocenyl systems within extended conjugated systems is reported, alongside in‐depth cyclic voltammetry, UV/Vis/near‐infrared (NIR) spectroelectrochemistry and X‐ray crystallography characterisation.